Profiling mentally ill offenders in Hong Kong: A 10‐year retrospective review study. (13th December 2021) - Siu, Bonnie Wei Man; Lai, Eric Shek Kin; Lam, Jessica Pui Yan; Chan, Clement; Chan, Anita Wai Lan; Chu, Kin Yan; Leong, Sek Lim; Lui, Sing Heung; Liu, Amy Ching Yung; Tang, Dorothy Yuen Yee; So, Wai Lam; Leung, Hon Wah; et al.
Abstract: Introduction: This study aimed to analyze the estimated prevalence of mental disorders among offenders and compare the estimated crime rate between mentally ill patients and the total population in Hong Kong. Methods: Service data of offenders referred to psychiatrists at the Siu Lam Psychiatric Centre from January 2011 to December 2020 were analyzed. Demographic data of gender, age on admission, educational level, principal psychiatric diagnosis, index offense, and assessment outcome were collected. Results: Data of 7535 offenders (74.8% males) aged 14 to 97 (mean: 41.3 ± 13.7) years were analyzed. More than 60% (66.2%) had a diagnosable mental disorder. The most prevalent principal psychiatric diagnosis was schizophrenia and related disorder (22.8%), followed by mental and behavioral disorders due to psychoactive substance use (18.6%), and mood disorders (8.8%). The commonest index offenses were theft and related offenses (20.5%), followed by acts intended to cause injury (19.7%), and illicit drug offenses (11.6%). The estimated prevalence of mental illness among prison population was 7.1% (male: 8.2%, female: 5.0%). The estimated crime rate for mentally ill patients was found to be 43.3 to 263.2 per 100 000 population. Discussion: The estimated prevalence of mental disorders among offenders and the estimated crime rate for mentally ill patients are relatively low in Hong Kong. The result was an important effort to document the changing characteristics of mentally ill offenders and provide an estimation of the prevalence and crime rate for mentally ill patients in Hong Kong.